Transition of care from paediatric to adult age for rare chronic disorders: an Italian experience. (30th September 2020) - Olivero, E; Bert, F; Corezzi, M; Corsi, D; Dominici, S; Scarmozzino, A; Siliquini, R
Abstract: Background: Transition of care represents the transfer from child to adult care. An effective transition maintains continuity of care and presents better clinical outcomes. Thanks to improved survivorship of chronic paediatric patients to adulthood, this process has assumed growing relevance. Aim of the study was to evaluate quality and effectiveness of transition of care model of one of the biggest Hospitals of Northern Italy, that has organised a common structured model, differentiated according to patients' clinical and social complexity. Methods: The sample consisted of patients with chronic rare diseases transited within the Hospital in the years 2016-2019. To analyse the evolution of all pathologies, for each patient the medical record was consulted; questionnaires were then administered to patients to investigate their illness perception and quality of life. Results: The average age at transition of the retrospective study patients was 19.8±4.7 years. For most disorders, 100% of patients made the first post-transition visit. More than 90% of patients who did not make further post-transition visits were patients with Neurofibromatosis 1. Only 7 out of 18 patients with NF1 continued their treatment to the indicated specialist. One-year drop-out was 13%. Regarding the perception of one's own illness, 78% of respondents consider their health status from good to excellent, but more than 30% of respondents believe not to have currently adequate psychological and social support. Conclusions: Transition of care represents an important phase in chronic diseases management. The proposed model assures a multidisciplinary approach, involving all specialists of both paediatric and adult teams. Preliminary data were positive and showed how this model could be an example for other institutions in Europe. Anyway, the transition model might be still be improved. Our data underlined the importance of a complete taking charge, with peculiar attention to psychological and social support. Key messages: The study shows to the European Healthcare Providers the importance of a personalized planning of transition of care, that considers the complexity of clinical situation and concomitant social issues. A successful strategy of transition of care requires a multidisciplinary approach, that guarantees a complete taking charge, with peculiar attention to psychological and social support.